PELATIHAN PEMBUATAN BUSINESS PLAN GUNA MEMBANGUN PELUANG BISNIS BAGI REMAJA DI DESA RIDOGALIH - Anhar, Siti Aulia; Ekowati, Ekowati; Qintharah, Yuha Nadhirah (An-Nizam, 2024)
A business plan is an important first step in developing a business because it contains basic guidelines for running a business, a summary of goals and details of how to achieve these goals. This KKN program aims to provide socialization on simple business plans to teenagers in Ridogalih Village, with a focus on economic problems in the area. The aim of this program is to provide a basic understanding of business concepts, inspire and guide teenagers in developing business ideas, and provide practical guidance in starting a simple business. Through this approach, it is hoped that it can increase business opportunities for teenagers in Ridogalih Village and make a positive contribution to local economic development and the welfare of the village community as a whole. The result of this activity show enthusiasm in planning and starting a business among teenangers in Ridogalih Village.